CURRENT EVIDENCE ON PLATELET-RICH PLASMA (PRP) IN THE MANAGEMENT OF UPPER LIMB TENDINOPATHIES - Paweł Szajewski; Justyna Kącikowska; Justyna Łapicka; Alicja Pełszyk; Natalia Kruszewska; Natalia Ziółkowska; Michał Cholewiński; Agata Pluta; Daria Marciniak; Natalia Rosół (International Journal of Innovative Technologies in Social Science, 2026)
Platelet-rich plasma (PRP) is an autologous blood derivative enriched in platelets and growth factors, increasingly utilized to enhance tendon healing in upper limb tendinopathies. This review systematically examines current evidence on PRP’s biological mechanisms and clinical efficacy in managing tendinopathies affecting the shoulder, elbow, and wrist. PRP exerts multifactorial effects by modulating inflammation, stimulating tenocyte proliferation, angiogenesis, and extracellular matrix remodeling. Clinical studies demonstrate PRP’s potential to reduce pain and improve function in rotator cuff tendinopathy, biceps tendinopathy, lateral and medial epicondylitis, and De Quervain’s tenosynovitis. Evidence also suggests PRP’s role as an adjunct in post-surgical tendon healing, facilitating earlier recovery and functional gains. However, heterogeneity in preparation methods and treatment protocols necessitates further standardized trials to optimize therapeutic outcomes.